The Impact of Emotional Responses on Female Reproduction: Fibrinolysis in the Spotlight - Hoirisch-Clapauch, Silvia (Seminars in Thrombosis and Hemostasis, 2024)
Fibrinolytic enzymes modify various substrates required for tissue remodeling, playing a crucial role in mechanisms underlying resilience, reward processing, ovulation, embryo implantation, and placentation. Individuals with low resilience and reduced reward responsiveness, when exposed to chronic stress, are at increased risk of experiencing a range of negative emotions. Chronic anxiety and melancholia are examples of negative emotions associated with hypercortisolism, while fear and atypical depression are characterized by systemic inflammation. Both cortisol and inflammatory cytokines stimulate the production of plasminogen activator inhibitor-1 (PAI-1), a potent fibrinolysis inhibitor. Chronic anxiety, fear, and depression are among the many hypofibrinolytic conditions increasing the risk of oligo-anovulation, miscarriage, fetal growth restriction, and preeclampsia. Although significant, the impact of negative emotions on implantation is not as obvious as on ovulation or placentation. Other hypofibrinolytic conditions that may affect female reproduction through mechanisms dependent or independent of PAI-1 include metabolic disturbances (e.g., due to consumption of highly palatable foods, often used to alleviate negative affect), inflammation, hyperhomocysteinemia, hypothyroidism, hypercortisolism, antiphospholipid antibodies, and the 4G allele of the PAI-1 gene. Benzodiazepines and antidepressants should be used with caution in the first trimester as this combination may cause malformations. Also, selective serotonin reuptake inhibitors have fibrinolytic properties that increase the risk of bleeding after surgical procedures. Psychological interventions, especially group therapy, are effective in the prevention of reproductive disorders. Controlled trials are needed to test the hypothesis that female reproductive health depends on psychological well-being, a balanced diet and physical activity, suppression of inflammation and autoantibodies, and homocysteine and hormonal homeostasis.
Keywords: emotions; ovulation; embryo implantation; miscarriage; fetal growth restriction